2018
DOI: 10.1177/1179554918794672
|View full text |Cite
|
Sign up to set email alerts
|

A Single Institution Experience of Incorporation of Cisplatin into Adjuvant Chemotherapy for Patients With Triple-Negative Breast Cancer of UnknownBRCAMutation Status

Abstract: The clinical benefit of adding platinum to adjuvant chemotherapy for patients with triple-negative breast cancer (TNBC) has not been well investigated, although it was associated an improved response rate in neoadjuvant setting. We retrospectively analyzed the time to tumor progression (TTP) and overall survival (OS) of patients with resected stage I-III TNBC who were treated with or without cisplatin-containing chemotherapy (CisCT or noCisCT) during 2004 and 2010. Of 129 patients, 25 received CisCT. In univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…91 An increased tumor pathological complete response (pCR) was shown in 53.2% of the patients with stage II-III triple-negative breast cancer (TNBC) treated with carboplatin against 36.9% without carboplatin. 92 In the BrighTNess trial, the pCR rate in TNBC increased from 31% without carboplatin to 58% with carboplatin. 92 In gastric cancer, a high amount of TAMs before treatment correlated with prolonged survival in patients who received 5-fluorouracil (FU)-based postoperative chemotherapy.…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…91 An increased tumor pathological complete response (pCR) was shown in 53.2% of the patients with stage II-III triple-negative breast cancer (TNBC) treated with carboplatin against 36.9% without carboplatin. 92 In the BrighTNess trial, the pCR rate in TNBC increased from 31% without carboplatin to 58% with carboplatin. 92 In gastric cancer, a high amount of TAMs before treatment correlated with prolonged survival in patients who received 5-fluorouracil (FU)-based postoperative chemotherapy.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…92 In the BrighTNess trial, the pCR rate in TNBC increased from 31% without carboplatin to 58% with carboplatin. 92 In gastric cancer, a high amount of TAMs before treatment correlated with prolonged survival in patients who received 5-fluorouracil (FU)-based postoperative chemotherapy. 76 In patients with stage III colorectal cancer treated with 5-FU adjuvant therapy, the high macrophage density before the treatment significantly correlated with a better improved prognosis.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…As a traditional chemotherapeutic drug, Cisplatin (DDP) has remarkable anti-tumor effect and wide antitumor spectrum, and is widely used in the treatment of various solid tumors (16). The main target site of Cisplatin is DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials showed mixed results for the treatment of TNBC with cisplatin with convoluted mechanisms [3][4][5][6][7]. To identify potential targets associated with the cisplatin resistance (cisplatin sensitive and resistant) due to unavailable datasets for TNBC, we adopted an ovarian cancer bioinformatics model.…”
Section: Upregulated Gene Expressions Of Egfr and Hypoxia Associate Wmentioning
confidence: 99%
“…Recent clinical trials have showed efficacy of cisplatin in combinational chemotherapy in comparison to conventional chemotherapeutic approaches for the treatment of TNBC [3][4][5]. However, others have demonstrated lackluster outcomes, and underlying mechanisms remain convoluted [6,7].…”
Section: Introductionmentioning
confidence: 99%